Assembling Hexahedral Supramolecular Nano‐Aggregates on Rice Wax Layer Matrices to Promote the Leaf Deposition and Bioavailability of Bactericides for Plant Protections - Run Yang; Jinghan Yang; Min Liu; Juan Liu; Peiyi Wang (Advanced Science)
Abstract Naturally hydrophobic wax layer microstructures in plants seriously hinder the leaf adhesion and deposition of pesticide droplets, thereby causing low pesticide bioavailability and inevitable environmental pollution. Inspired by the supramolecular self‐assembly strategy, two anisotropic supramolecular building units (BiTA18@β‐CD and BiTA18@γ‐CD) are invented based on the host–guest complexation between a benzimidazole‐modified bactericidal molecule (BiTA18) and β‐/γ‐cyclodextrin (β‐CD/γ‐CD), which self‐assemble into nano‐sized hexagonal cuboids on the rice microcrystalline matrix. This consequence markedly enhances the retention of bactericidal ingredients on target plants. More intriguingly, these oligosaccharide‐coated supramolecular materials, with superior biocompatibility, can break through the bacterial biofilm barrier, limit bacterial motility and extracellular enzyme secretion, and induce electrolyte leakage and ROS accumulation in bacteria, ultimately annihilating the stubborn pathogenic bacterium. Combining these excellent advantages, the optimal supramolecular material (BiTA18@β‐CD) displays broad‐spectrum and efficient control efficacies of 54.4% and 71.7% against rice bacterial blight and citrus bacterial canker, respectively, surpassing those of kasugamycin (34.3%/34.1%), thiodiazole‐copper‐20%SC (39.9%/42.7%), and BiTA18 (42.7%/46.9%) at 200 µg mL−1. Besides, the current supramolecular systems are safe for non‐target organisms like earthworms and zebrafishes. This study provides a key inspiration for the construction of supramolecular building units assembled on rice microcrystalline substrates to improve the utilization of pesticides.